Molecular footprints of selective pressure in the neuraminidase gene of currently circulating human influenza subtypes and lineages - Correia, Vanessa (2019)
Influenza neuraminidase (NA) is under selective pressure (SP) of both host immune system and drug use. Here, we assembled large datasets of NA sequences of worldwide circulating viruses to estimate the global and site-specific SP acting on all current subtypes/lineages of human influenza NA. An overall negative SP of similar magnitude and a prevalence of negatively selected sites were observed for all subtypes/lineages. Positively selected sites varied according to the subtype/lineage, including N1-NA sites 247 and 275, N2-NA sites 148 and 151, and B/Victoria-NA site 395 associated with drug-resistance or reduced susceptibility. These results evidenced a potential role of positive selection in the low-level spread of A(H1N1)pdm09-H275Y drug-resistant viruses, and alerted for a potential higher risk of spread of a synergistic A(H1N1)pdm09 drug-resistant variant (H275Y/S247N). The positive selection detected at N2-NA sites 148 and 151 was probably an artefact from cell-culture. Overall mapping revealed six potential new druggable regions.